UCP1 Dependent and Independent Thermogenesis in Brown and Beige Adipocytes - Ikeda, Kenji; Yamada, Tetsuya (Frontiers in Endocrinology, 2020)
Mammals have two types of thermogenic adipocytes: brown adipocytes and beige adipocytes. Thermogenic adipocytes express high levels of uncoupling protein 1 (UCP1) to dissipates energy in the form of heat by uncoupling the mitochondrial proton gradient from mitochondrial respiration. There is much evidence that UCP1 is the center of BAT thermogenesis and systemic energy homeostasis. Recently, UCP1 independent thermogenic pathway identified in thermogenic adipocytes. Importantly, the thermogenic pathways are different in brown and beige adipocytes. Ca2+-ATPase 2b calcium cycling mechanism is selective to beige adipocytes. It remains unknown how the multiple thermogenic mechanisms are coordinately regulated. The discovery of UCP1-independent thermogenic mechanisms potential offer new opportunities for improving obesity and type 2 diabetes particularly in groups such as elderly and obese populations who do not possess UCP1 positive adipocytes.